PENERAPAN MANAJEMEN REKAM MEDIS SESUAI DENGAN LEGALITAS PADA FISIOTERAPI MANDIRI DI KOTA PEMATANGSIANTARUDUL - Isa Harpika Br. Ginting; Noni Herawati; Fransius P. Sinaga (Yayasan Nusantara Hasana Berdikari, 2025)
This study examines the implementation of medical record management in accordance with regulations and legality at independent physiotherapy facilities located in Pematangsiantar City. This community service study was conducted using a descriptive analytical approach using observation, interviews, questionnaires, and documentation methods. The research findings indicate that there are significant gaps in medical record management, where some practitioners have not fully complied with applicable health regulations, as shown by previous research in the Semarang area which indicated that 37.1% of physiotherapists did not carry out medical record recording properly. In addition, the implementation of an Electronic Medical Record (EMR) system is seen as a strategic solution to optimize service quality, increase patient data accessibility, and meet service standards stipulated in the Minister of Health Regulation. This article presents a series of findings, analysis, and recommendations to improve compliance and efficiency of medical record management in independent physiotherapy clinics, as well as providing an overview of the process and challenges faced in its implementation.